Shift Work and Circadian Dysregulation of Reproduction - Gamble, Karen L.; Resuehr, David; Johnson, Carl (Frontiers in Endocrinology, 2013)
Health impairments, including reproductive issues, are associated with working nights or rotating shifts. For example, shift work has been associated with an increased risk of irregular menstrual cycles, endometriosis, infertility, miscarriage, low birth weight or pre-term delivery, and reduced incidence of breastfeeding. Based on what is known about circadian regulation of endocrine rhythms in rodents (and much less in humans), the circadian clock is an integral regulatory part of the reproductive system. When this 24-h program is disordered by environmental perturbation (such as shift work) or genetic alterations, the endocrine system can be impaired. The purpose of this review is to explore the hypothesis that misalignment of reproductive hormones with the environmental light-dark cycle and/or sleep wake rhythms can disrupt menstrual cycles, pregnancy, and parturition. We highlight the role of the circadian clock in regulating human reproductive physiology and shift work-induced pathology within each step of the reproductive axis while exploring potential mechanisms from the animal model literature. In addition to documenting the reproductive hazards of shift work, we also point out important gaps in our knowledge as critical areas for future investigation. For example, future studies should examine whether forced desynchronization disrupts gonadotropin secretion rhythms and whether there are sleep/wake schedules that are better or worse for the adaptation of the reproductive system to shift work. These studies are necessary in order to define not only whether or not shift-work induced circadian misalignment impairs reproductive capacity, but also to identify strategies for the future that can minimize this desynchronization.